Stock Returns following Large One‐Day Declines: Evidence on Short‐Term Reversals and Longer‐Term Performance - COX, DON R.; PETERSON, DAVID R. (Journal of Finance, 1994)
ABSTRACT We examine stock returns following large one‐day price declines and find that the bid‐ask bounce and the degree of market liquidity explain short‐term price reversals. Further, we do not find evidence consistent with the overreaction hypothesis. We observe that securities with large one‐day price declines perform poorly over an extended time horizon.